PSYCHOLOGICAL CONTENT OF DEVELOPING SCIENTIFIC RESEARCH COMPETENCES OF MASTER'S STUDENTS - Usmanova Umida Aybekovna (Modern American Journals, 2025)
This article discusses the pedagogical and psychological content of developing scientific research competencies of master's students . It also shows that master's students should be aware of the content of scientific approaches, concepts, theories, and the latest information in their discipline during their studies at a higher educational institution and their subsequent professional development.
Keywords: Innovation, science, scientific and pedagogical activity, research, scientific research, discovery, self-awareness, scientific conferences, intellectual-developmental.